2022
DOI: 10.1038/s41598-022-12544-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of leptospirosis among patients attending renal and general outpatient clinics in Mulago Hospital, Kampala, Uganda

Abstract: In this study, we sought to establish the prevalence of leptospirosis among renal patients and general outpatients attending Mulago National Referral Hospital, Uganda. A total of 254 patients were recruited, their blood samples collected and interviewer-administered semi-structured questionnaires provided between July and October 2018. These questionnaires captured data on sociodemographic characteristics and symptoms of leptospirosis disease. An individual with an average body temperature of 37.3 ± 1.1 °C was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…On the other hand, the findings of this study showed the presence of some participants prior to exposure to Leptospira bacteria due to their antibodies reacting to MAT titers, which ranged from 1:20 to 1:80, below the cut-off point of significance. This result agreed with the study of [30], which concluded the presence numbers of participants' prior exposure to Leptospira infection. These conditions occur probably due to the routine practice of healthcare workers in primary and secondary levels of treatment to suggest the frequency of uses of recommended antibiotics among non-malarial febrile patients that may be un-diagnosed.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…On the other hand, the findings of this study showed the presence of some participants prior to exposure to Leptospira bacteria due to their antibodies reacting to MAT titers, which ranged from 1:20 to 1:80, below the cut-off point of significance. This result agreed with the study of [30], which concluded the presence numbers of participants' prior exposure to Leptospira infection. These conditions occur probably due to the routine practice of healthcare workers in primary and secondary levels of treatment to suggest the frequency of uses of recommended antibiotics among non-malarial febrile patients that may be un-diagnosed.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this study revealed that the overall seroprevalence of human leptospirosis was 7.7%, which was in line with the previous studies in different parts of the world, including northern Tanzania, with a prevalence of 8.8% [16,26] and northeastern Malaysia, with a seroprevalence of 8.4% [27]. However, this study's seroprevalence was higher than the findings reported from Nepal (4.8%) [28], Mozambique (1.3%) [29], and Uganda 4.7% [30]. In contrast, the study prevalence was lower compared to a prevalence of 13% reported in Kilosa district, Tanzania [31], 14.7 % in Ecuador [32], 21% in Nepal [33], 11.2% in northern Peru [34], and 46.3% reported in Japan [35].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For East Sub-Saharan Africa, annual morbidity of 91,100 cases per 100,000 population has been reported [6]. In Uganda, Leptospira exposure has been shown in febrile patients from geographically distinct areas [7][8][9][10]. Domestic animals, particularly cattle and pigs are speculated as the source of these human Leptospira exposures [7,8,10], despite evidence of exposure in other main reservoirs such as wildlife [11].…”
Section: Introductionmentioning
confidence: 99%